KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, DAN PEMANFAATAN TEKNOLOGI TERHADAP PEMAHAMAN AKUNTANSI PADA PROSES PEMBELAJARAN DARING - Artha Pratiwi, Kadek Eliska Insani; Wahyu Purna Angara, I Wayan Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.05.TAHUN.2023, 2023)
Online learning is another option implemented by policymakers during the coronavirus pandemic. This test intends to provide empirical data on the impact of intellectual and emotional intelligence and the use of technology in the world of accounting education during the Covid-19 pandemic. This test was carried out within the Faculty of Economics and Business, Udayana University. This test uses a sample of 10 people. Data collection is carried out using questionnaires. The applied method of data analysis is multiple linear regression. The test results show that the impact of intellectual intelligence and the use of technology has a negative impact, while emotional intelligence has a positive effect on online accounting education during the pandemic